(untitled) (Indian Journal of Public Health Research & Development, 2020)
The health concern of the alcoholic beverages has remained a key issue to be addressed to the consumers. The aim of the present study was to assess the antioxidant activity and cytotoxicity of the selected 22 bottled commercial alcoholic brands widely consumed in the Maharashtra state of India. The result of the present study shows that the brands of wines followed by whiskies and rums were more effective as free radical scavenging agents, containing considerable amount of polyphenols. Overall, the vodaka brands were observed to be more cytotoxic as compared to other brands. With few exceptions, there exists a positive correlation in the amount of polyphenols and free radical scavenging activity, while the former was negatively correlated with cytotoxicity.